Community development banking: A proposal to establish a nationwide system of community development banks - Hyman P. Minsky; Dimitri B. Papadimitriou; Ronnie J. Phillips; L. Randall Wray (Levy Economics Institute of Bard College, 1993)
This brief proposes that the establishment of a nationwide system of community development banks (CDBs) would advance the capital development of the economy. The proposal is based on the notion that a critical function of the financial system is not being adequately performed by existing institutions for low-income citizens, inner-city minorities, and entrepreneurs who seek modest financing for small businesses. The primary goals of the CDBs are to deliver credit, payment, and savings opportunities to communities not well served by banks, and to provide financing throughout a designated area for businesses too small to attract the interest of the investment banking and normal commercial banking communities.
Keywords: 330